SMART–C3: An Integrated TPS-3R Cluster Model for Circular Economy and Zero-Waste Management in Bali, Indonesia - Regine Antonette Loresto; Sheralyn De Las Nieves; Yohanes Parlindungan Situmeang; Florabel Nieva; Maris Alida Mores; I Gede Pasek Mangku; Ida Bagus Komang Mahardika; Putu Gede Bayu Janardhana Dusak; Desak Ayu Praweri; Yuliana Evangelista Ina Ose Lamadorok (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The research evaluates the operational performance, challenges, and developmental potential of the TPS-3R waste management system in Tangkas Village, Bali, and introduces the SMART–C³ Model as a solution to improve sustainability and operational efficiency. Utilizing a qualitative descriptive methodology, the study gathered data through interviews with key stakeholders, including village officials, TPS-3R managers, sanitation workers, and community members, as well as field observations of waste management activities and document analysis. The results indicate that while the facility handles approximately 38–40 tons of waste monthly, its success is limited by inconsistent household segregation, high residual waste generation, infrastructure constraints, workforce shortages, and weak institutional enforcement. Public participation remains moderate, particularly regarding segregation and recycling efforts. Additionally, the study identifies that although the Organic Waste Recycling Center provides valuable secondary processing, it is not effectively integrated into the overall system. Differing from conventional TPS-3R practices, this study proposes the SMART–C³ Model, which incorporates smart monitoring, cluster-based processing, segregation-based collection, and community-focused behavioral change within a unified circular-economy framework. This scalable, community-driven approach enhances stakeholder participation and resource recovery while reducing reliance on landfills, offering a robust strategy for reaching zero-waste targets in rural and semi-urban regions. Contribution to Sustainable Development Goals (SDGs): SDG   6: Clean Water and Sanitation; SDG 11: Sustainable Cities and Communities; SDG 12: Responsible Consumption and Production; SDG 13: Climate Action; SDG 15: Life on Land